Research on the New R&D Institutions in Wuhan. (October 2019) - Ge, Shi; Tao, Huang
Abstract: As a powerful organizational driving force to promote innovation and development of the international community, the new R&D institutions are increasingly becoming a new entry point for achieving double breakthroughs in technological innovation and economic development. Based on the definition and the cause of formation of the new R&D institutions, this paper analyses the characteristics and operation mode of the new R&D institutions in Wuhan. Then, this paper puts forward some suggestions and prospects on the problems of Wuhan's new R&D institutions.